Investigation of characteristics of Kenaf/PLA filament for ankle foot orthosis using fused deposition modelling - Shahar, Farah Syazwani (2021)
Additive manufacturing had been taking a lot of attraction for the past several years and had been implemented in various fields including the Prosthetics and Orthotics industry. One of the applications is the Ankle-Foot Orthosis (AFO), which has an increase in demand in the recent years. However, most of the current materials used to manufacture AFO were made from plastics, which are non-biodegradable, wastes many fabrication materials, and not cost-effective. Thus, this highlights the aim of this research, which is to develop a lightweight AFO using Kenaf/PLA composite and 3D printing technology. This research consists of two phases, which is the experimental phase, and the numerical phase (FEA simulation). The experimental phase of the research will start with the development of Kenaf/PLA filament with different level of extrusion temperature (160°C, 170°C, 180°C, 190°C, 200°C) and fiber loading (0 wt. %, 3 wt. %, 5 wt. %, 7 wt. %), followed by physical and thermal testing of the filament, then fabrication of Kenaf/PLA composite using Fused Deposition Modelling (FDM) printer, and finally, mechanical and physical testing of 3D printed Kenaf/PLA specimens. As for the numerical analysis phase, it consists of two types of analysis, which are the static structural analysis and explicit dynamic analysis. In static structural analysis, the study will be specifically on three extreme gait stages, which are heel strike, midstance, and heel rise. As for explicit dynamic analysis, only the selected AFO composites material and PLA AFO will be studied and compared. The results of this research are consist of the effect of extrusion temperature on the physical structure of filament and the smoothness of the extrusion process, physical and thermal analysis of the filament extruded at the selected temperature, mechanical and physical properties of 3D printed Kenaf/PLA, as well as the comparison of strength between neat PLA AFO and the selected variation of Kenaf/PLA AFO. The result shows filament extruded at 170°C has the best physical structure and ease of extrusion process. The thermal analysis of the selected filament shows a reduction of temperature points in filament composites compared to a neat PLA. Based on the FEA simulation of static structural analysis, it was also found 3 wt. % Kenaf/PLA AFO shows better total deformation, equivalent stress, and equivalent strain compared to PLA AFO and AFO made from other variation of Kenaf/PLA. Meanwhile, the explicit dynamic simulation result shows that 3D printed Kenaf/PLA AFO could retain the strength shown by neat PLA AFO. In addition, since the fabrication of the plaster mold was skipped and the design of AFO could be optimized digitally, material waste was reduced significantly.